Tuberculosis of breast in a woman with history of prolactinoma (a case report) - Gh Ghorbani; F Tavakoli (JRI, 2002)
Tuberculosis (TB) contains a broad range of clinical illnesses. It is the most frequent cause of death worldwide. TB was a global public health emergency from 1993 for world health organization. The world health organization estimated the eradication of tuberculosis until year of 2000, when detected the drug’s for tuberculosis treatment. But in later years AIDS pandemic increased the tuberculosis. Tuberculosis causes most of the time lung complication but also can infect other organs as well. Breast tuberculosis is a very rare infection that can be mistaken with breast cancer.This is a case report of female patient with 25 years age who has prolactinoma from three years ago and has milky and epudative discharge since one year ago. She had medical and surgical drainage. Since there was no response to treatment, biopsy was taken and pathologic evaluation demonstrated the granuloma with caseosis. Patient was treated with antituberculosis drug and there was no recurrent for one year follow up.
Keywords: Breast mass, Tuberculosis, Caseosis granuloma, prolactinoma